Complete Resolution of Central Serous Chorioretinopathy Cases Treated with Low Power Mode Laser Technology : A Novel Approach: Poster Presentation - Case Series - Resident - Setiawan, Grace; Virgana, Rova; Widyanatha, Made Indra; Ihsan, Grimaldi; Kartasasmita, Arief Sjamsulaksan; Iskandar, Erwin (Majalah Oftalmologi Indonesia, 2023)
Introduction : Central serous chorioretinopathy (CSC) is an idiopathic condition mostly affecting men in their 20s to 50s. It is characterized by serous fluid accumulation behind the neurosensory retina resulting in a localized macular detachment. Aldosterone-receptor antagonist and photodynamic laser therapy are the current mainstay of treatments, although most CSC cases can resolves spontaneously within 2 to 3 months. Low power mode (LPM) laser has emerged as a new effective technology to treat CSC. Case Illustration : Case 1: A 50-year-old male was diagnosed with recurrent chronic CSC since 2 months ago. His visual acuity declined even after given oral aldosterone receptor antagonist for two weeks, so he was scheduled to undergo LPM. After three weeks of laser treatment, CSC resolved and the visual acuity improved (Figure1). Case 2 : A 47-year-old male complained of decreased vision and metamorphopsia on his right eye since two weeks ago. He was diagnosed with CSC and underwent LPM. Three weeks after LPM, his vision improved and the metamorphopsia resolved (Figure2). LPM helps the migration of retinal pigment epithelium (RPE) cells to restore the outer blood-retinal barrier through expression of heat shock proteins. We used MC-500ViXi laser system (Nidek Co., Gamagori, Japan) and the laser parameters used in this study were 100?m spot size, 0.01s exposure time, 0.25-0.5 spacing, and 30% LPM ratio. Discussion : Conclusion : LPM is a new yet promising treatment modalities to treat acute and chronic CSC. Its low power nature makes LPM a safe choice of treatment with less damage to the surrounding retina.